2021
DOI: 10.3390/en14133779
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of the Lack of Contact in Plate and Fin and Tube Heat Exchanger on Heat Transfer Efficiency under Periodic Flow Conditions

Abstract: Plate fin-tube heat exchangers are widely used in air conditioning and refrigeration systems and other industry fields. Various errors made in the manufacturing process can result in the formation of an air gap between the tube and fin. Several numerical simulations were carried out for a symmetric section of plate fin-tube heat exchanger to study the influence of air gap on heat transfer under periodic flow conditions. Different locations and sizes of an air gap spanning 1/2 circumference of the tube were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…They also presented diagrams with the Colburn factors for low Reynold numbers. Łęcki et al [12] presented a comparison between HTCs obtained using CFD simulation to the one calculated with VDI correlation for three-row inline PFTHE. Sadeghianjahromi et al [13] determined HTCs and pressure drop factors of PFTHEs with different fin types and circular and flat tubes under dry and wet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They also presented diagrams with the Colburn factors for low Reynold numbers. Łęcki et al [12] presented a comparison between HTCs obtained using CFD simulation to the one calculated with VDI correlation for three-row inline PFTHE. Sadeghianjahromi et al [13] determined HTCs and pressure drop factors of PFTHEs with different fin types and circular and flat tubes under dry and wet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the manufacturing process, errors can lead to the formation of an air gap between the tube and fin. The effect of the air gap on heat transfer was studied by Łęcki et al [4] using numerical simulations for a symmetric section of the heat exchanger under periodic flow conditions. The results showed that the fin discontinuity along the circumference reduces the heat transfer rate compared to the perfect fin-tube contact case.…”
Section: Heat Transfer and Heat Exchangersmentioning
confidence: 99%
“…Numerical research revealed that the heat transfer coefficient of circular tubes was approximately 18% higher than that of flat tubes, and the pressure drop generated under the same conditions was moderate (approximately 10%). In 2021, Marcin et al [15] studied the influence of air gaps on heat transfer under periodic flow conditions through numerical simulations of symmetrical section plate fin tube heat exchangers. Blocking the heat flow by the gap reduces the heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%